Evaluation of mechanical vapor recompression in the reactive distillation of the N-butanol esterification process (Research, Society and Development, 2021)
The process of producing esters is usually performed through esterification in a reactor followed by a distillation column to separate the products. However, this design limits the reagent conversion. Reactive distillation is an alternative to get around this issue as it allows greater reagent conversions in reactions limited by chemical equilibrium. It is one of the most famous process intensification techniques. On the other hand, mechanical vapor recompression has been used to recycle waste heat to improve efficiency of conventional distillation columns. In this context, this work evaluated the inclusion of a mechanical vapor recompression system in a reactive distillation process to obtain n-butyl acetate via n-butanol esterification with acetic acid. Systems with and without recompression were simulated in an Aspen Plus™ environment. The addition of recompression resulted in a reduction of 33.65% in the annual cost of the process, while not significantly affecting the purity of the desired product and the reagents’ conversion. From an environmental point of view, the mechanical vapor recompression system adoption resulted in a 12.69% reduction in CO2 emissions, contributing positively to meeting the requirements of the environmental regulations.